Study of Affecting Factors of Meteorological Parameters on Solar Radiation in Kathmandu Valley (The Batuk, 2020)
Solar radiation data are great significance for solar energy systems. This study aimed to estimate monthly and seasonal average daily global solar radiation on a horizontal surface in Kathmandu (27.7oN, 85.5oE, 1350 masl), Nepal, by using CMP6 pyranometer in 2012. The influence of the global solar irradiation from different physical as well as meteorological parameters was analyzed. Besides this, the research highlighted that there is high level of fluctuation of the measured value of global solar irradiance due to local weather conditions. As a result of this measurement, the maximum, minimum monthly and yearly mean solar radiation values were (21.32 ± 4.14) MJ/m2/day in May,(10.93 ± 2.03) MJ/m2/day in January and (16.68 ± 4.60)MJ/m2/day found respectively. Annual average of clearness index, maximum temperature, minimum temperature, relative sunshine hour, air mass are 0.51 ± 0.12, (26.23 ± 4.96)oC, (12.38 ± 6.83)oC, 0.57 ± 0.165 and 1.54 ± 0.42 respectively. There is positive correlation of maximum temperature and negative correlation of air mass with global solar radiation.